2019
DOI: 10.1186/s12884-019-2392-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for pregnancy related complications among urban slum and non-slum women in Bangladesh

Abstract: Background Bangladesh is facing a higher maternal mortality and morbidity than many other developing countries in the world. The majority of these maternal deaths occur due to pregnancy related complications. Although health facilities in urban areas in Bangladesh are widely available, women living in underprivileged urban areas are least likely to receive the maternal health services and as a result, they face more pregnancy related complications. Unfortunately, there are only a few studies on co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 10 publications
4
30
0
Order By: Relevance
“…This result is in line with the results of research in several countries which found that people who live in urban areas tend to have better health status. The tendency for better health status in this urban area is found in South Africa [13], India [14], Bangladesh [15][16], and Iran [17].…”
Section: Discussionmentioning
confidence: 91%
“…This result is in line with the results of research in several countries which found that people who live in urban areas tend to have better health status. The tendency for better health status in this urban area is found in South Africa [13], India [14], Bangladesh [15][16], and Iran [17].…”
Section: Discussionmentioning
confidence: 91%
“…Safe motherhood programs try to alleviate some of this burden of ignorance and encourage proper planning among families to prepare for birth and allocate resources for any complications that may arise. [ 2 4 6 ] Obstetric emergencies have exhaustive effects on the mother and fetus which can cause significant maternal and fetal/infant morbidity and mortality. Maternal mortality is a vital index of the quality and efficiency of obstetric services prevailing in a country.…”
Section: Discussionmentioning
confidence: 99%
“…Common obstetric issues seen in ED are hyperemesis gravidarum, abortions, eclampsia/preeclampsia, etc., Nonobstetric causes include urinary tract infections including pyelonephritis, lower respiratory tract infections, acute undifferentiated febrile illnesses, deep venous thrombosis, etc. [ 2 4 ] Majority of the emergencies in these women have been found to be symptoms suggestive of a miscarriage, some of which can be prevented if early and efficient treatment is instituted. Improved access to preventive care in India, particularly in rural areas, could be beneficial to countering high rates of maternal and child morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, global urbanization has become a major concern. As with many other developing countries, Bangladesh is facing various challenges due to urbanization in the last few decades [1]. About 67% of the urban population growth of Bangladesh is caused by the influx of rural residents migrating to cities for economic opportunities [2].…”
Section: Introductionmentioning
confidence: 99%